KETERAMPILAN BERARGUMENTASI ILMIAH PADA PEMBELAJARAN FISIKA MELALUI MODEL PEMBELAJARAN INKUIRI TERBIMBING - Mahardika, Andi Ichsan; Fitriah, Fitriah; Zainuddin, Zainuddin (Vidya Karya Jurnal Kependidikan, 2015)
This research aims to develop the scientific skill in making argumentation by guided inquiry model in two aspects: (1) to describe the argumentation skill in physics learning, (2) to describe the implimentation of physics learning by guided inquiry model. This research design is one group pretest posttest design. The subject research is the eleventh grade students of Mathematics and Natural Sciences in 21 students and Phyisics teachers of eleventh grade. Â The data collection is argumentation test and observation sheet. The analysis technique is gain score, percetage, and reliability. The research result states that the guided inquiry model is effective to increase the argumentation skill in Physics learning.